Current topics in osteoporosis - Deng, Hong-wen (World Scientific, 2005)
This book reviews important topics in osteoporosis, with the emphasis on both clinical management and basic research of the disease. From the clinical perspective, topics covering pathogenesis, diagnosis, and treatment of osteoporosis are extensively elaborated. Several more chapters complement clinical overview of osteoporosis, that discuss the effects of nutrition and exercise to bone health, the application of biochemical markers in osteoporosis diagnosis, novel potential drug targets for osteoporosis treatment, and osteoporosis in males and in children. As the prevalence of osteoporosis no.